Heart motion measurement with three dimensional sonomicrometry and acceleration sensing - Horiuchi, Tetsuya (2012)
In robotic assisted beating heart surgery, the goal is to develop a robotic system that can actively cancel heart motion by closely following a point of interest (POI) on the heart surface, a process called Active Relative Motion Canceling (ARMC). In order to track and cancel POI motion precisely, control algorithms require good quality heart motion data. In this paper, a novel method is described which uses a particle filter to estimate the three-dimensional location of POI on heart surface by using measurements obtained from sonomicrometry along with an accelerometer. The new method employs a differential probability approach to increase the accuracy of the particle filter. The performance of the proposed method is evaluated by simulations.